The instruments for measuring students’ self-efficacy in biology learning: Validity and reliability - Rahmi, Yosi Laila; Hayati, Miftahul (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2021)
Creating a valid and reliable instrument is very necessary to produce a quality and accountable research. A research instrument must also be able to meet the requirements so that what you want to measure can produce accurate data. This study aims to develop a standard and quality instrument for measuring students’ s self-efficacy in Biology learning. The method used in this research is descriptive quantitative with the aim of knowing the quality of the items on the three dimensions of self-efficacy, namely the dimensions of level, strength, and generality, that it can be used to measure the self-efficacy of students in learning biology. The instrument used is a self-efficacy questionnaire consisting of 40 statements. Sample in this research is 20 students in grade XI MIPA SMAN 2 Hiliran Gumanti. The items in instrument analysis test, was conducted by a validator, namely through professional judgment or expert review. The data analysis technique used is the validity test using Pearson's Product Moment analysis and the reliability test using the Chronbach Alpha technique. The results of the study and data analysis showed that the instrument for measuring students' self-efficacy was valid and reliable. So, it can be concluded that the research instrument meets the criteria for use in the next analysis, because it can measure students' self-efficacy even though there are several items that must be revised first.